Readiness Assessment for Literacy Program Implementation: A Case Study of Elementary Schools - Nurhasanah, Nurhasanah; Rustan, Edhy; Mahmud, Hilal (International Journal of Asian Education, 2025)
This study examines the readiness of elementary schools in Palopo City, Indonesia, for implementing literacy programs under the Merdeka Curriculum framework. Using a mixed-methods approach and the Countenance Stake evaluation model, the study assesses key antecedents, including school policies, infrastructure, and instructional strategies. Data were collected from nine selected schools through observations, interviews, surveys, and document analysis. Findings reveal that while school policies align with national regulations, such as Ministry of Education Regulation No. 56/M/2022, inconsistencies in implementation persist due to resource constraints and uneven Standard Operating Procedures (SOPs). Infrastructure limitations, including inadequate library facilities, poorly maintained reading corners, and insufficient multimedia resources, hinder literacy-rich environments. Schools employ strategies, such as teacher training, reading programs, and stakeholder collaborations, to address these gaps. However, disparities in access to professional development and unequal resource distribution highlight ongoing challenges. This study underscores the importance of policy standardization, infrastructure enhancement, and targeted capacity-building programs to foster sustainable literacy practices. Strengthening school-community partnerships and increasing government support are crucial for addressing systemic gaps. The findings contribute to the discourse on literacy education in Indonesia, offering practical recommendations for policymakers and educators. Literacy programs can be more effectively implemented by improving school readiness, supporting national educational goals and enhancing student learning outcomes.